A REVIEW ON NEOPLASTIC DISEASES AND THEIR TREATMENT - Ayush Singh; Gurpinder Singh; Manju; Deepak Singh Charak; Neeru Kumari (Indian Journal of Integrative Medicine, 2022)
Cancer is a serious health problem and a complex genetic disorder that continues to be the leading cause of death worldwide, usually caused by carcinogens. Carcinogens can be present in the air, water, food, chemicals and sunlight that people are exposed too. In leukemia, the body produces large amounts of abnormal white blood cells. Improved knowledge of the molecular mechanism underlying cancer progression has led to the development of a large number of cancer drugs. New strategies and new chemopreventive agents are needed to complement current cancer therapies to increase efficacy. In this review, the author generally elaborates on several types of cancer-related disorders that occur in children and adults. In this review article, the first-line drugs/drugs used in anti-neoplastic drug therapy and the main toxic effects of first-line drugs are discussed.